Intermediate filament associated proteins - Wilson, Katherine L.; Sonnenberg, Arnoud (Methods in enzymology, 2016)
Intermediate Filament Associated Proteins, the latest volume in the Methods in Enzymology series, continues the legacy of this premier serial with quality chapters authored by leaders in the field. This volume covers research methods in intermediate filament associated proteins and contains sections on such topics as lamin-associated proteins, intermediate filament-associated proteins and plakin, and other cytoskeletal cross-linkers.